(untitled) (مجلة كلية العلوم الاسلامية, 2018)
Praise be to God, prayer and peace be upon the Prophet Muhammad, peace be upon him and his family and companions and followed them until the Day of religion either: Thus, through the review of the issue of the extent of faith and search, we find it important the issue of fundamentalism, they are of the pillars of faith are not true to their faith, and therefore our duty to the extent of faith and stick with it because it is the basis of this life. The most important thing rid him of this research is to answer the question raised of old, newly raised, that: it should not be talking in the pot matters at all, arguing that it is a matter of doubt and uncertainty, and that the door still its feet, and lost it understood at. The answer for this: that the prohibition set out the position on the following matters: 1_ go into much vanity, and without knowledge there is no evidence. 2_ rely on to know the fate of the human mind minor. It 3_ leaves the delivery and compliance to God Almighty _ _ in the capacity. 4_ Find the hidden side in the pot. 5 _ interceptors questions which may not be reflected: like telling intransigent: Why the guidance of Allah So and so, and so and so astray? And why God instructed man among the other creatures? And why God Flana richest and poorest Flana? And so on. . . , And asked = from Mstvhma there is nothing wrong; is health of sample question, asked of the obstinate _ is not consistent learner _ that it does not solve a few asked not in large (). 6_ conflict in the pot: which leads to different people in it, and in Afteragahm would, then it is forbidden to him.